Inovação em empresas com certificação de sustentabilidade: elementos determinantes de sua convergência - Ruggi, Maíra Oliveira (2018)
This thesis aims to identify how the innovation activities undertaken by companies certified by B Lab act on the sustainability actions of these organizations. Understanding the concern of these organizations with sustainability, it is to expect that innovation also taking into account the creation of products, processes or methods less socially and environmentally impacting. In order to verify these aspects, the theoretical reference discussed concepts of sustainability, certification of sustainability, innovation and sustainable innovation. In addition, a survey was conducted with organizations certified by B LAB, a non-profit organization created in the United States that certifies companies for their social and environmental performance standards, transparency, and legal accountability. Data collection was done through a questionnaire made available electronically to the 1,968 companies certified by B LAB, 191 of them answered the survey, from 27 different countries. The results indicate that there is an impact of the innovations and eco-innovations developed by the companies in the sustainability pillars. In general, the radical, incremental and product/service innovations typology positively impacted the pillars, this study didn’t find significant relationship between radical innovation and the social pillar. In relation to product/service innovation, the strongest correlation is with the economic pillar, then the environmental pillar and finally the social pillar. Eco-innovations, on the other hand, have different behavior, with a greater positive correlation for the environmental pillar, then social and lastly economic. The results also pointed out that for this sample there are three distinct groups of companies: the environmental trend, with a smaller number, social and economic trend, with more number and companies that give importance to the triple bottom line. There are also positive correlations between innovation strategies with innovations and eco-innovations, in addition to the identification that few companies in the sample are eco-innovators, and to realize that the reasons that led companies to innovate impacted on the triple bottom line.